Biological characters of human dermal fibroblasts derived from foreskin of male infertile patients. Issue 1 (February 2017) - Fang, Fang; Ni, Ke; Cai, Yiting; Ye, Zhen; Shang, Jin; Shen, Shiliang; Xiong, Chengliang
Highlights: Dermal fibroblasts derived from human foreskin expressed intermediate filament protein vimentin and nestin. The isolated dermal fibroblasts expressed mesenchymal surface markers CD73, CD90, CD44 and CD105, and were negative for haematopoietic markers CD45 and CD34. Cryopreservation had no influence on morphology and growth properties of the isolated dermal fibroblasts. Abstract: Dermal fibroblasts play a vital role in maintaining skin function. They not only synthesize and secrete extracellular matrix molecules, but also produce a complex mixture of bioactive factors, which both contribute to immune regulation and wound healing. Fibroblasts isolated from skin tissue exhibit wide range of potentials, especially in regenerative medicine. The use of fibroblast cultures for medical purposes requires standardization of cell preparations. To achieve this, we isolated and characterized dermal fibroblasts from human foreskin with a standardized method. The obtained cells grew as typical morphology of fibroblasts, and expressed intermediate filament protein vimentin and nestin. Immunophenotypic analysis indicated that the isolated fibroblasts expressed mesenchymal surface markers CD73, CD90, CD44 and CD105, and were negative for haematopoietic markers CD45 and CD34. Growth kinetics analysis of the cells showed high proliferative properties. Furthermore, cryopreservation had no influence on cell morphology and growth properties. Here, we describe a standardized, repeatable method for isolation of fibroblasts from human foreskin tissues and identify their biological characters according to morphologic, immunohistologic and proliferative criteria, which would be meaningful for future clinical trials and regenerative medicine purposes.